Immunologic Evaluation of Pediatric Chronic and Recurrent Acute Rhinosinusitis. Issue 1 (January 2020) - Li, Carol; Peng Hwa, Tiffany; Schussler, Edith; Pearlman, Aaron N.
Background: Although pediatric rhinosinusitis is a commonly encountered clinical entity, the diagnostic approach and treatment algorithm are constantly evolving. In addition to anatomic and allergic etiologies, immunologic deficiencies have been implicated in the pathogenesis of rhinosinusitis; however, the prevalence of immunologic disease in pediatric rhinosinusitis is poorly defined. Objective: To inform the approach to the evaluation of pediatric patients with rhinosinusitis, this retrospective pilot study examined the prevalence of abnormal results detected on immunologic testing in pediatric patients with chronic rhinosinusitis (CRS) and recurrent acute rhinosinusitis (RARS). Methods: Patients between 2008 and 2018 were identified using International Classification of Diseases 9/10 codes. Imaging, endoscopy findings, and clinical criteria were used to diagnose CRS and RARS (n = 27). We reviewed available results, including quantitative immunoglobulins (Igs), thyroid evaluation, complete blood count, and titers to Streptococcus, Haemophilus influenzae type B (HiB), Diphtheria, and Tetanus. Statistical analyses were performed with the Mann–Whitney U test and Fisher's exact test. Results: Our initial search yielded 140 patients, of which 27 met diagnostic criteria for CRS (17) or RARS (10). Eight patients (29.6%) underwent adenoidectomy and 5 (18.5%) underwent endoscopic sinus surgery. The most common Ig deficiencies were IgM, 13.0%, and IgA, 11.1%. Four (23.5%) of the 17 patients had significantly elevated IgE levels, indicating a possible allergic etiology. Within this cohort, there was an increased incidence of insufficient protective titers to polysaccharide vaccines. HiB titers were not protective in 35% of our cohort. Insufficient pneumococcal protection was more common in patients >10 years, while deficient IgM was more common in those <10 years. Conclusion: High-yield testing in pediatric rhinosinusitis should include titers to polysaccharide antigens, specifically Streptococcus pneumoniae and H. influenzae . Low-yield tests that may be deferred during initial testing include thyroid studies and Tetanus and Diphtheria antibodies. Prospective, high-volume studies are required to further elucidate the role of immunologic testing in this population.